2016
DOI: 10.1037/hea0000239
|View full text |Cite
|
Sign up to set email alerts
|

“Priming” hand hygiene compliance in clinical environments.

Abstract: This is one of the first studies to demonstrate that priming can influence HHC in a clinical setting. The findings suggest that priming interventions could be used to change other behaviors relevant to public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 21 publications
2
109
2
5
Order By: Relevance
“…In face-to-face settings, direct looks of a source-as compared to evasive glances-increased compliance with a request (Guéguen & Jacob, 2002), and cues to being watched-like a picture of a pair of eyes-instigated cooperative behavior (Bateson, Nettle, & Roberts, 2006). For example, placing a photo of eyes above a soap dispenser at hospitals increased hand hygiene, as people felt observed and obliged to comply with hygienic standards (e.g., King et al, 2016). Accordingly, eye-gazing and posture of a performer on a screen might instigate similar effects, as they enhance users' illusion of taking part in a real social interaction.…”
mentioning
confidence: 99%
“…In face-to-face settings, direct looks of a source-as compared to evasive glances-increased compliance with a request (Guéguen & Jacob, 2002), and cues to being watched-like a picture of a pair of eyes-instigated cooperative behavior (Bateson, Nettle, & Roberts, 2006). For example, placing a photo of eyes above a soap dispenser at hospitals increased hand hygiene, as people felt observed and obliged to comply with hygienic standards (e.g., King et al, 2016). Accordingly, eye-gazing and posture of a performer on a screen might instigate similar effects, as they enhance users' illusion of taking part in a real social interaction.…”
mentioning
confidence: 99%
“…To improve the immersive nature of the scenario being practiced, realism is improved by mimicry of the sights, sounds and tactile sensations participants might experience in a real-world scenario, and scenarios are designed to be emotionally realistic. Smell is rarely used during medical simulations, though it has the potential to alter the behaviour of participants,12 16 to further improve simulator validity,1 3 13 to assist in biographical memory formation9 17 18 and to desensitise trainees to strong malodours 7 8 19. We carried out a systematic review of literature relating to the use of smell in medical simulation training.…”
Section: Discussionmentioning
confidence: 99%
“…Smells have also been used with success in virtual restorative environments, which use smell to enhance the validity of virtually generated environments, though the therapeutic effects of smells are out with the scope of this review 10 16 18 22. The use of smells to prompt certain behaviours via unconscious mechanisms, such as those shown by Birnbach et al ,12 also has much potential in the clinical setting 16…”
Section: Discussionmentioning
confidence: 99%
“…Our research team recently demonstrated that the hand hygiene of visitors to a surgical intensive care unit was significantly enhanced through specific olfactory and visual primes (King et al. ).…”
Section: Mindspace In Actionmentioning
confidence: 99%